Protective adhesive tape for power battery shell and preparation method of protective adhesive tape

By using modified Elosite nanotubes and thermal stabilizers in the protective tape for power battery case, combined with dopamine self-polymerization technology, the problem of insufficient thermal stability and mechanical properties of the existing tape is solved, significantly improving the performance of the tape and ensuring the safety of the battery.

CN119752337AActive Publication Date: 2025-04-04HUNAN ZHAOYING NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510003675.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing protective tape used in power battery case has shortcomings in thermal stability and mechanical properties, which may lead to safety problems such as short circuits in the battery or spontaneous combustion.

Method used

The substrate layer including PET resin, modified elolite nanotubes, thermal stabilizers, coupling agents, antioxidants and pigments is used to obtain polydopamine-coated elolite nanotubes through dopamine self-polymerization, and combined with the thermal stabilizer to improve the mechanical properties and thermal stability of the tape.

Benefits of technology

It significantly improves the mechanical properties and thermal stability of the protective tape for power battery case, reduces the risk of battery short circuit and spontaneous combustion, and meets higher market demand.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesive tapes, and particularly relates to a protective adhesive tape for a power battery shell and a preparation method thereof. The protective adhesive tape for the power battery shell comprises a release layer, a base material layer and an adhesive layer which are sequentially arranged, wherein the base material layer comprises the following raw materials in parts by weight: 30-40 parts of PET resin, 3-5 parts of modified halloysite nanotubes, 1-4 parts of a heat stabilizer, 0.5-1 part of a coupling agent, 0.3-0.5 part of an antioxidant and 0.5-1 part of pigment. The modified halloysite nanotube contained in the adhesive tape can improve the overall mechanical property of the adhesive tape, and the heat stabilizer can improve the heat stability of the adhesive tape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesive tapes, and in particular relates to a protective adhesive tape for a power battery casing and a preparation method thereof. Background Art

[0002] With the development of science and technology and the enhancement of environmental awareness, new energy vehicles are gradually playing an important role in people's lives. Power batteries, which provide power sources, are the core components of new energy vehicles. Their safety plays a vital role in the safety of new energy. In the preparation process of power batteries, tape is usually used to wrap the outer shell of the power battery to fix the internal components.

[0003] In addition, the tape can also separate the battery cells from each other to avoid the impact of a single battery cell failure on other battery cells. It can be seen that the tape is crucial in the preparation process of power batteries. With the rapid development of the new energy vehicle industry, the demand for power batteries has increased significantly. There is a greater market demand for protective tapes used in power battery casings, but at the same time, higher requirements are placed on the performance of the protective tapes. However, the tapes on the market usually have problems such as poor thermal stability and mechanical properties, which may cause safety issues such as battery short circuits and even spontaneous combustion. Based on this, it is necessary to further explore and improve the performance of protective tapes for power battery casings. Summary of the invention

[0004] The first object of the present invention is to provide a protective tape for a power battery casing, the tape having excellent mechanical properties and thermal stability.

[0005] The second object of the present invention is to provide a method for preparing a protective tape for a power battery casing, which is simple and easy to practice.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A protective tape for a power battery housing, the protective tape comprising a release layer, a substrate layer and an adhesive layer arranged in sequence, the substrate layer comprising the following raw materials in parts by weight: 30-40 parts of PET resin, 3-5 parts of modified halloysite nanotubes, 1-4 parts of a thermal stabilizer, 0.5-1 parts of a coupling agent, 0.3-0.5 parts of an antioxidant, and 0.5-1 parts of a pigment;

[0008] The preparation process of the modified halloysite nanotubes is as follows:

[0009] (1) adding halloysite nanotubes to a Tris-dopamine hydrochloride solution for stirring and reacting, and purifying to obtain pretreated halloysite nanotubes after the reaction is completed;

[0010] (2) dispersing sodium alginate in anhydrous ethanol, and then adding sodium periodate to react, and after the reaction is completed, purifying and drying to obtain oxidized sodium alginate;

[0011] (3) adding the pretreated halloysite nanotubes in step (1) into water, and then adding oxidized sodium alginate to react, and purifying after the reaction to obtain modified halloysite nanotubes.

[0012] Furthermore, in step (1), the solid-to-liquid ratio of the halloysite nanotubes to the Tris-dopamine hydrochloride solution is (0.1-0.2) mg:1 mL; the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2-3 mg / mL; the temperature of the stirring reaction is 40-60° C., and the stirring reaction time is 24-36 h.

[0013] Furthermore, in step (2), the mass ratio of sodium alginate to sodium periodate is 1:(2-4); the molecular weight of the sodium alginate is 10-20KD; and the reaction is specifically carried out at room temperature in the dark for 8-12 hours.

[0014] Furthermore, in step (3), the mass ratio of oxidized sodium alginate to pretreated halloysite nanotubes is 1:(0.1-0.5); and the reaction time is 10-12 hours.

[0015] Furthermore, the preparation process of the thermal stabilizer is as follows:

[0016] The hydroxylated graphene is added to an aqueous solution of polyacrylic acid for heating reaction to obtain the product.

[0017] Furthermore, the molar ratio of the hydroxylated graphene to the polyacrylic acid is 1:(2-5); the temperature of the heating reaction is 60-70° C., and the heating reaction time is 6-8 hours.

[0018] Furthermore, the coupling agent is a silane coupling agent, the antioxidant is a hindered phenol antioxidant, and the pigment is a cobalt blue pigment.

[0019] Furthermore, the silane coupling agent is trimethoxy(propyl)silane, and the hindered phenol antioxidant is 3,5-di-tert-butyl-4-hydroxybenzoic acid.

[0020] Furthermore, the thickness of the release layer is 0.5-1.5 μm, the thickness of the substrate layer is 20-40 μm, and the thickness of the adhesive layer is 15-35 μm. A method for preparing the protective tape for a power battery housing comprises the following steps:

[0021] i. According to the weight ratio, the raw materials of the substrate layer are uniformly mixed, and the substrate layer is obtained by melt extrusion and calendering;

[0022] ii. coating a non-silicone release agent solution on one side of the substrate layer in step i, and curing the solution in an oven to obtain a release layer;

[0023] iii. Apply polyacrylate adhesive on the other side of the substrate layer in step i, and cure it in an oven to obtain an adhesive layer. After cooling, cut and roll it up.

[0024] Furthermore, in step ii, the curing temperature is 70-80°C, and the curing time is 10-15 minutes; in step iii, the curing temperature is 80-90°C, and the curing time is 45-50 minutes.

[0025] The beneficial technical effects of the present invention are:

[0026] The present invention obtains polydopamine-coated halloysite nanotubes, i.e., pretreated halloysite nanotubes, by self-polymerization of dopamine. The surface of the pretreated halloysite nanotubes contains abundant amino functional groups, which can react with the aldehyde functional groups in the oxidized sodium alginate, thereby improving the overall mechanical properties of the adhesive tape. The thermal stabilizer can improve the compatibility of graphene in the substrate, thereby improving the thermal stability of the substrate. In addition, the modified halloysite nanotubes are used in combination with the thermal stabilizer to further improve the thermal stability of the substrate. DETAILED DESCRIPTION

[0027] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0028] The preparation process of hydroxylated graphene of the present invention is:

[0029] Take 1L of 1.5g / L graphene oxide aqueous solution, add ammonia water after ultrasonication for 30min and adjust the pH of the solution to 7.5 to obtain a mixed solution; add 2.0g of hydrazine hydrate to the mixed solution, transfer to a 90°C oil bath, condense and reflux for 32h, then adjust the oil bath temperature to 80°C, add 2.0g of aminophenylethanol and 2.5g of isoamyl nitrite to the mixed solution, condense and reflux for 36h, filter to neutrality, and then freeze-dry for 5d to obtain hydroxylated graphene.

[0030] The non-silicone release agent solution involved in the present invention is PEELOIL 1010.

[0031] 1. Embodiment

[0032] Example 1

[0033] A protective tape for a power battery shell, the protective tape comprising a release layer, a substrate layer and an adhesive layer which are arranged in sequence, the substrate layer comprising the following raw materials in parts by weight: 33 parts of PET resin, 4 parts of modified halloysite nanotubes, 2 parts of a thermal stabilizer, 0.7 parts of trimethoxy(propyl)silane, 0.4 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 0.8 parts of a cobalt blue pigment.

[0034] The preparation process of the modified halloysite nanotubes is as follows:

[0035] (1) adding the halloysite nanotubes to the Tris-dopamine hydrochloride solution at a solid-liquid ratio of 0.15 mg:1 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2.4 mg / mL, stirring and reacting at 50° C. for 30 h, and after the reaction is completed, filtering, washing, and drying to obtain pretreated halloysite nanotubes;

[0036] (2) Dispersing sodium alginate (molecular weight 12KD) in anhydrous ethanol according to the mass ratio of sodium alginate to sodium periodate of 1:3, then adding sodium periodate, reacting at room temperature in the dark for 10 hours, and after the reaction is completed, purifying and drying to obtain oxidized sodium alginate;

[0037] (3) adding the pretreated halloysite nanotubes prepared in step (1) to water at a mass ratio of oxidized sodium alginate to pretreated halloysite nanotubes of 1:0.4, and then adding oxidized sodium alginate to react for 11 hours. After the reaction is completed, the modified halloysite nanotubes are purified to obtain the modified halloysite nanotubes.

[0038] The preparation process of the above heat stabilizer is as follows:

[0039] According to the molar ratio of hydroxylated graphene to polyacrylic acid of 1:3, hydroxylated graphene is added to the aqueous solution of polyacrylic acid, and reacted at 65°C for 7h to obtain the product.

[0040] The preparation method of the protective tape for the power battery shell is as follows:

[0041] i. According to the weight ratio, the raw materials of the substrate layer were mixed uniformly, placed in a twin-screw extruder, the screw speed was set to 120 rpm, the head temperature was 160 ° C, and the melt extrusion was calendered to obtain a substrate layer with a thickness of 30 μm;

[0042] ii. coating a non-silicon release agent solution on one side of the substrate layer in step i, and curing it in an oven at 75° C. for 12 minutes to obtain a release layer with a thickness of 1 μm;

[0043] iii. Apply polyacrylate adhesive on the other side of the substrate layer in step i, and cure it in an oven at 85°C for 48 minutes to obtain an adhesive layer with a thickness of 20 μm. After cooling, cut and roll it up.

[0044] Example 2

[0045] A protective tape for a power battery shell, the protective tape comprising a release layer, a substrate layer and an adhesive layer which are arranged in sequence, the substrate layer comprising the following raw materials in parts by weight: 40 parts of PET resin, 5 parts of modified halloysite nanotubes, 4 parts of a thermal stabilizer, 1 part of trimethoxy(propyl)silane, 0.5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 1 part of a cobalt blue pigment.

[0046] The preparation process of the modified halloysite nanotubes is as follows:

[0047] (1) adding the halloysite nanotubes to the Tris-dopamine hydrochloride solution at a solid-liquid ratio of 0.2 mg:1 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 3 mg / mL, stirring and reacting at 60° C. for 24 h, and after the reaction is completed, filtering, washing, and drying to obtain pretreated halloysite nanotubes;

[0048] (2) dispersing sodium alginate (molecular weight 20KD) in anhydrous ethanol at a mass ratio of sodium alginate to sodium periodate of 1:4, then adding sodium periodate, reacting at room temperature in the dark for 12 hours, and after the reaction is completed, purifying and drying to obtain oxidized sodium alginate;

[0049] (3) adding the pretreated halloysite nanotubes prepared in step (1) into water at a mass ratio of oxidized sodium alginate to pretreated halloysite nanotubes of 1:0.5, and then adding oxidized sodium alginate to react for 12 h. After the reaction is completed, the modified halloysite nanotubes are purified to obtain the modified halloysite nanotubes.

[0050] The preparation process of the above heat stabilizer is as follows:

[0051] According to the molar ratio of hydroxylated graphene to polyacrylic acid of 1:5, hydroxylated graphene is added to the aqueous solution of polyacrylic acid, and reacted at 70°C for 6h to obtain the product.

[0052] The preparation method of the protective tape for the power battery shell is as follows:

[0053] i. According to the weight ratio, the raw materials of the substrate layer were mixed uniformly, placed in a twin-screw extruder, the screw speed was set to 120 rpm, the head temperature was 160 ° C, and the melt extrusion was calendered to obtain a substrate layer with a thickness of 20 μm;

[0054] ii. coating a non-silicon release agent solution on one side of the substrate layer in step i, and curing it in an oven at 80° C. for 10 min to obtain a release layer with a thickness of 0.5 μm;

[0055] iii. Apply polyacrylate adhesive on the other side of the substrate layer in step i, and cure it in an oven at 90°C for 45 minutes to obtain an adhesive layer with a thickness of 15 μm. After cooling, cut and roll it up.

[0056] Example 3

[0057] A protective tape for a power battery shell, the protective tape comprising a release layer, a substrate layer and an adhesive layer which are arranged in sequence, the substrate layer comprising the following raw materials in parts by weight: 30 parts of PET resin, 3 parts of modified halloysite nanotubes, 1 part of a thermal stabilizer, 0.5 parts of trimethoxy(propyl)silane, 0.3 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, and 0.5 parts of cobalt blue pigment.

[0058] The preparation process of the modified halloysite nanotubes is as follows:

[0059] (1) adding the halloysite nanotubes to the Tris-dopamine hydrochloride solution at a solid-liquid ratio of 0.1 mg:1 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2 mg / mL, stirring and reacting at 40° C. for 36 hours, and after the reaction is completed, filtering, washing, and drying to obtain pretreated halloysite nanotubes;

[0060] (2) dispersing sodium alginate (molecular weight 10KD) in anhydrous ethanol according to the mass ratio of sodium alginate to sodium periodate of 1:2, then adding sodium periodate, reacting at room temperature in the dark for 8 hours, and after the reaction is completed, purifying and drying to obtain oxidized sodium alginate;

[0061] (3) adding the pretreated halloysite nanotubes prepared in step (1) into water at a mass ratio of oxidized sodium alginate to pretreated halloysite nanotubes of 1:0.1, and then adding oxidized sodium alginate to react for 10 h. After the reaction is completed, the modified halloysite nanotubes are purified to obtain the modified halloysite nanotubes.

[0062] The preparation process of the above heat stabilizer is as follows:

[0063] According to the molar ratio of hydroxylated graphene to polyacrylic acid of 1:2, hydroxylated graphene is added to the aqueous solution of polyacrylic acid, and reacted at 60°C for 8h to obtain the product.

[0064] The preparation method of the protective tape for the power battery shell is as follows:

[0065] i. According to the weight ratio, the raw materials of the substrate layer were mixed uniformly, placed in a twin-screw extruder, the screw speed was set to 120 rpm, the head temperature was 160 ° C, and the melt extrusion was calendered to obtain a substrate layer with a thickness of 40 μm;

[0066] ii. coating a non-silicon release agent solution on one side of the substrate layer in step i, and curing it in an oven at 70° C. for 15 min to obtain a release layer with a thickness of 1.5 μm;

[0067] iii. Apply polyacrylate adhesive on the other side of the substrate layer in step i, and cure it in an oven at 80°C for 50 minutes to obtain an adhesive layer with a thickness of 35 μm. After cooling, cut and roll it up.

[0068] 2. Comparative Example

[0069] Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 1 is that halloysite nanotubes are used instead of modified halloysite nanotubes.

[0071] Comparative Example 2

[0072] The difference between Comparative Example 2 and Example 1 is that polydopamine and halloysite nanotubes are used instead of modified halloysite nanotubes, the mass ratio of halloysite nanotubes to polydopamine is 0.15:2.4, and the other preparation conditions are the same as those in Example 1.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that the preparation process of the modified halloysite nanotubes is changed. The details are as follows:

[0075] Steps (2) to (3) are omitted, that is, pretreated halloysite nanotubes are used instead of modified halloysite nanotubes, and the remaining preparation conditions are the same as those in Example 1.

[0076] Comparative Example 4

[0077] The difference between Comparative Example 4 and Example 1 is that graphene is used instead of the thermal stabilizer.

[0078] 3. Test examples

[0079] Tensile strength and elongation at break: The tensile strength and elongation at break of the adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 were tested using a universal tensile test machine. The test temperature was room temperature, the effective test length of each sample was 100 mm, and the test speed was 10 m / min. The results are shown in Table 1.

[0080] Heat resistance: The tapes prepared in Examples 1-3 and Comparative Examples 1-4 were pasted on a clean stainless steel plate and baked in a constant temperature oven at 150°C for 4 hours. The tapes were peeled off in the oven while hot and the stainless steel plate was observed for any residual adhesive. The heat resistance of each tape was evaluated. The results are shown in Table 1.

[0081] Table 1

[0082] Tape / Performance Tensile strength(MPa) Elongation at break (%) Residual glue traces Example 1 196.2 116.8 No residual glue Example 2 195.0 116.1 No residual glue Example 3 193.8 115.6 No residual glue Comparative Example 1 163.3 92.4 Slight adhesive residue Comparative Example 2 169.6 100.2 Slight adhesive residue Comparative Example 3 178.1 103.7 Slight adhesive residue Comparative Example 4 191.7 114.3 Serious adhesive residue

[0083] It can be seen from Table 1 that the adhesive tapes prepared in Examples 1-3 have excellent mechanical properties and high thermal stability.

[0084] Compared with Examples 1-3, Comparative Example 1 uses halloysite nanotubes instead of modified halloysite nanotubes, and Comparative Examples 2-3 adjust the preparation process of modified halloysite nanotubes, which significantly reduce the mechanical properties of the resulting tape. Analysis shows that the present invention obtains polydopamine-coated halloysite nanotubes, i.e., pretreated halloysite nanotubes, by self-polymerization of dopamine. The surface of the pretreated halloysite nanotubes contains abundant amino functional groups, which can react with the aldehyde functional groups in oxidized sodium alginate to form covalent bonds. This chemical bonding significantly enhances the interfacial bonding force between the halloysite nanotubes and the matrix material. Stronger interfacial bonding indicates that when the tape is subjected to external force, it is not easy for the halloysite nanotubes to debond from the matrix, thereby improving the overall mechanical properties of the tape.

[0085] Compared with Examples 1-3, the thermal stability of the tapes in Comparative Examples 1-3 is reduced, and the thermal stability of the tape prepared in Comparative Example 4 using graphene instead of the thermal stabilizer is significantly reduced. The above results show that the thermal stabilizer of the present invention can improve the compatibility of graphene in the substrate, thereby improving the thermal stability of the substrate. In addition, the use of modified halloysite nanotubes in combination with the thermal stabilizer can further improve the thermal stability of the substrate.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A protective tape for a power battery housing, characterized in that: The protective tape comprises a release layer, a substrate layer and an adhesive layer arranged in sequence, wherein the substrate layer comprises the following raw materials in parts by weight: 30-40 parts of PET resin, 3-5 parts of modified halloysite nanotubes, 1-4 parts of thermal stabilizer, 0.5-1 parts of coupling agent, 0.3-0.5 parts of antioxidant, and 0.5-1 parts of pigment; The preparation process of the modified halloysite nanotubes is as follows: (1) adding halloysite nanotubes to a Tris-dopamine hydrochloride solution for stirring and reacting, and purifying to obtain pretreated halloysite nanotubes after the reaction is completed; (2) dispersing sodium alginate in anhydrous ethanol, and then adding sodium periodate to react, and after the reaction is completed, purifying and drying to obtain oxidized sodium alginate; (3) adding the pretreated halloysite nanotubes in step (1) into water, and then adding oxidized sodium alginate to react, and purifying after the reaction to obtain modified halloysite nanotubes.

2. The protective tape for power battery housing according to claim 1, characterized in that: The solid-to-liquid ratio of the halloysite nanotubes and the Tris-dopamine hydrochloride solution in step (1) is (0.1-0.2) mg:1 mL; the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2-3 mg / mL; the temperature of the stirring reaction is 40-60° C., and the stirring reaction time is 24-36 h.

3. The protective tape for a power battery housing according to claim 1, characterized in that: The mass ratio of sodium alginate to sodium periodate in step (2) is 1:(2-4); the molecular weight of the sodium alginate is 10-20KD; and the reaction is specifically carried out at room temperature in the dark for 8-12 hours.

4. The protective tape for a power battery housing according to claim 1, characterized in that: In step (3), the mass ratio of oxidized sodium alginate to pretreated halloysite nanotubes is 1:(0.1-0.5); and the reaction time is 10-12 hours.

5. The protective tape for a power battery housing according to claim 1, characterized in that: The preparation process of the thermal stabilizer is as follows: The hydroxylated graphene is added to an aqueous solution of polyacrylic acid for heating reaction to obtain the product.

6. The protective tape for a power battery housing according to claim 5, characterized in that: The molar ratio of the hydroxylated graphene to the polyacrylic acid is 1:(2-5); the temperature of the heating reaction is 60-70° C., and the heating reaction time is 6-8 hours.

7. The protective tape for a power battery housing according to claim 1, characterized in that: The coupling agent is a silane coupling agent, the antioxidant is a hindered phenol antioxidant, and the pigment is a cobalt blue pigment.

8. The protective tape for a power battery housing according to claim 1, characterized in that: The thickness of the release layer is 0.5-1.5 μm, the thickness of the substrate layer is 20-40 μm, and the thickness of the adhesive layer is 15-35 μm.

9. A method for preparing the protective tape for a power battery housing as claimed in claim 1, characterized in that: The following steps are involved: i. According to the weight ratio, the raw materials of the substrate layer are uniformly mixed, and the substrate layer is obtained by melt extrusion and calendering; ii. coating a non-silicone release agent solution on one side of the substrate layer in step i, and curing the solution in an oven to obtain a release layer; iii. Apply polyacrylate adhesive on the other side of the substrate layer in step i, and cure it in an oven to obtain an adhesive layer. After cooling, cut and roll it up.

10. The method according to claim 9, characterized in that The curing temperature in step ii is 70-80°C and the curing time is 10-15 minutes; the curing temperature in step iii is 80-90°C and the curing time is 45-50 minutes.

Citation Information

Patent Citations

  • Method for preparing organic / inorganic nano composite surface sizing agent

    CN103290725A

  • Preparation method of hydroxylated graphene powder with controllable conductive performance

    CN104310384A

  • Polydopamine-modified halloysite nanotube / polylactic acid composite material and preparation and application thereof

    CN105566872A

  • High-performance PET base film and preparation method thereof

    CN114410071A

  • High-toughness multifunctional sodium alginate-based nano composite material as well as preparation method and application thereof

    CN115368643A